Factor Of Consumers Attitude Toward Mobile Advertising - Sea, Su Yee (2014)
This study demonstrate the adaption of Theory of Reasoned Action (TRA), Technology Acceptance Model and Web Advertising Model to examine how technology-related factors and web advertising model influence Malaysian consumer's attitude toward mobile advertising and lead to consumer's purchase intention. A self-administered questionnaire was designed using establish scales. A survey on 124 respondents was conducted in Penang. Malaysia through email, restaurant and public university intercept methods.